Analisis Pengaruh Alat Audit dan Sistem Arsip terhubung dalam Mendukung Proses Audit Laporan Keuangan - Mohammad Afrizal Miradji; Nur Munzilatur Rohmah; Meytasya Shalsabella; Tasya Nurul Idlomia (Jurnal Kendali Akuntansi, 2024)
Digitalization and information technology have a significant impact on business processes. This problem can be solved through synthesis, which involves the use of new computing technologies. Picture books are one example of advances in information technology in the field of education. This research was conducted with the aim of finding out the effectiveness of using chart books in the process of managing financial records. The research method used is a qualitative summary based on theory, research results and conclusions reached. Research, historical information, and survey results are then collected, analyzed, and compiled. The study found that book charting applications play an important role in the purchasing process, with technology used in the review process through an integrated and automated system. In order for the documentation process to be more efficient and effective, it must comply with established standards and guidelines. Organizations are becoming more diverse and integrated. Improved analyst performance indicates that the commentator is trustworthy and knowledgeable, thereby improving overall quality. Based on this, we can conclude that the Diagram Book application helps in the financial report review process.